Unfinished demarcation: the Apinajé people’s struggle for the territory divided by the Trans-amazonian highway (Tempo e Argumento, 2023)
This article talks about the history of the Apinajé people's struggle for the indigenous territory excluded from the demarcation process in the 1980s. The ‘Gameleira lands’ were suppressed from the indigenous land by the boundary set by the Trans-Amazonian highway (BR-230), built in the 1970s, which ran through the indigenous territory. We begin by explaining aspects of the indigenous territorial and environmental management of demarcated and claimed lands, pointing out the Associação União das Aldeias Apinajé (Pempxà) as an interconnecting entity for the Apinajé people's political struggles. Next, we contextualize the construction of the Trans-Amazonian highway and its impacts on the Apinajé territory. Based on various documentary sources, we describe the lengthy struggle for demarcating the indigenous land, pointing out the influence of the highway and the pressures of regional elites in suppressing the areas to the west of the BR-230. Finally, we reconstruct ethnohistorical elements of the ‘Gameleira lands,’ demonstrating the various relationships established between the Apinajé people and this region. It is concluded that the justification for suppressing this territory no longer exists due to the deviation from the original route and that official documents reiterate the recognition of this Apinajé territory, while the struggle for demarcating the ‘Apinajé II’ area persists.
Keywords: Apinajé people; indigenous land; Trans-Amazonian highway